School Readiness of Ummul Habibah Pre-School Students in Klambir V Kebun Village measured by the Nijmeegse Schoolbekwaamheids Test (NST) - Munisa Munisa; Rita Nofianti; Naya Rama Andini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The reason readiness matters are that children who are prepared for school will advance in their development. The term